2022
DOI: 10.1084/jem.20220857
|View full text |Cite
|
Sign up to set email alerts
|

Engineering an inhibitor-resistant human CSF1R variant for microglia replacement

Abstract: Hematopoietic stem cell transplantation (HSCT) can replace endogenous microglia with circulation-derived macrophages but has high mortality. To mitigate the risks of HSCT and expand the potential for microglia replacement, we engineered an inhibitor-resistant CSF1R that enables robust microglia replacement. A glycine to alanine substitution at position 795 of human CSF1R (G795A) confers resistance to multiple CSF1R inhibitors, including PLX3397 and PLX5622. Biochemical and cell-based assays show no discernable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 84 publications
1
36
0
Order By: Relevance
“…Introducing a diverse microbiome in experimental mice, as done in the 'wildling' mice, has been shown to represent a much closer model to humans than using specificpathogen free mice and might be also important to study in the context of macrophage-targeted therapies 172,173 . Recent mouse studies using macrophage replacement models by using genetic or pharmacological inhibition of the colony-stimulating factor 1 receptor have shown promise for translation to patients, for example, in the context of replacing dysfunctional microglia during neurodegenerative diseases 231 . Finally, although in humanized mice the human immune system development can be recapitulated, the niche-specific imprinting on human macrophages will be derived from mouse tissues.…”
Section: Boxmentioning
confidence: 99%
“…Introducing a diverse microbiome in experimental mice, as done in the 'wildling' mice, has been shown to represent a much closer model to humans than using specificpathogen free mice and might be also important to study in the context of macrophage-targeted therapies 172,173 . Recent mouse studies using macrophage replacement models by using genetic or pharmacological inhibition of the colony-stimulating factor 1 receptor have shown promise for translation to patients, for example, in the context of replacing dysfunctional microglia during neurodegenerative diseases 231 . Finally, although in humanized mice the human immune system development can be recapitulated, the niche-specific imprinting on human macrophages will be derived from mouse tissues.…”
Section: Boxmentioning
confidence: 99%
“…The engulfment of WT microglia by A455D microglia following exposure to p-Tau is additionally substantiated by scRNA-seq ligand-receptor interaction analysis of the interplay between WT and A455D microglia. As demonstrated in recent studies 72,73,83,84 , efficient microglia replacement by peripheral cell sources or through direct microglia transplantation requires the treatment with destructive agents, such as CSF1R inhibitors and/or toxic preconditioning of the bone marrow niche. Our results suggest that in the context of AD, eliminating endogenous senescent/dystrophic microglia may not be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…6I). To elucidate the role of microglia in behavioral abnormalities of cKO/HFD mice, we took advantage of pharmacological microglia deletion using PLX3397, a colony-stimulating factor 1 receptor (CSF1R) inhibitor, to assess the consequence of microglia elimination on cognitive function and anxiety behavior (27)(28)(29). Results showed that PLX3397 treatment markedly reduced the num ber of Iba-1-positive microglia in the hippocampus (fig.…”
Section: Microglial Ffar4 Deletion Aggravates Neuroinflammation Cause...mentioning
confidence: 99%